(untitled) (Journal of the College of Basic Education, 2025)
The goal of the current research is to know the reasons for the reluctance of students of the College of Basic Education to enroll in the Special Education Department and the significance of the statistical differences in students’ estimates of the reasons for reluctance according to the variables of gender (males -females) and specialization (scientific - humanities) and the proposed solutions to address them. To achieve these goals, use the descriptive approach. The researcher built a questionnaire consisting of four areas and (24) items distributed equally among the areas, and for each item he set (5) answer alternatives (agree to a very large degree - agree to a large extent - agree to a moderate degree - agree to a degree below the average - strongly disagree) and grades are given. (5,4,3,2,1) After verifying the validity and reliability of the questionnaire, it was applied to 200 male and female students accepted as new students for the academic year 2024-2025 from four departments, two scientific departments (the Science Department and the Computer Department) and two humanities departments (the Arabic Department and the History Department), and from each specialty (100) male and female students (50). One female student and (50) male students randomly To verify the objectives of the research, arithmetic means and standard deviations were extracted for each paragraph of the questionnaire and for each field of research. It was found that the degree of reasons for students’ reluctance ranged between an average degree and a large degree on all areas of the questionnaire, as the general arithmetic mean reached (3.403) and the standard deviation reached (1.1286). The field of the special education teacher’s work environment ranked first, with arithmetic mean (3.528) and standard deviation (1.1358). The academic field ranked second, with arithmetic mean (3.493) and standard deviation (1.0521), and the social and family field ranked third, as The arithmetic mean was (3,313) and the standard deviation was (1,2212) The economic field ranked fourth, with arithmetic mean (3,278) and standard deviation (1,1055). The absence of statistically significant differences between the arithmetic averages of the sample members’ estimates on the tool is attributed to the variable (gender), and the presence of statistically significant differences attributed to the variable of specialization and in favor of scientific A set of proposed solutions was reached to solve the problem of the reluctance of students of the College of Basic Education to join the Special Education Department, and the most important of these solutions is (working to provide a stimulating and encouraging educational environment for the teacher to perform his role to the fullest extent). (Coordination between the Ministry of Higher Education and the labor market to provide new jobs for graduates of the Special Education Department in various state ministries such as the Ministry of Justice, the Ministry of Labor and Social Affairs, the Ministry of Youth and Sports, the Ministry of Education, the Ministry of Women and other ministries) and (for the university and college to carry out introductory and awareness campaigns about the specialization of special education. (Providing comprehensive health insurance and health and medical care for teachers of special education classes) and activating the role of educational guidance in schools to demonstrate the importance of people with special needs and how to care for them and integrate them into society and benefit from their energies in various areas of development) and (The contribution of the media and families in strengthening the status of the teacher and improving his image. professional, and social status) (Developing a strategy in which all ministries and state institutions participate in changing the awareness and prevailing culture about the special education teacher) and (disbursing material and moral incentives to students enrolled in the basic education colleges, special education department, especially the distinguished ones) and (increasing the salaries of special education classroom teachers by adding professional allowances. Especially for teachers of special education classes and (providing incentives and scholarships for students wishing to complete their graduate studies in the field of special education)